2021
DOI: 10.3390/ijerph18199957
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Weight Stigma, Physical Appearance Concerns, and Enjoyment and Tendency to Avoid Physical Activity and Sport

Abstract: Participation in physical activity and sport is on the decline and there is a poor understanding of the psychosocial factors that contribute to people’s reluctance to participate. We examined whether there were relationships between factors such as weight stigma, weight bias internalization, appearance evaluation, and fears of negative appearance evaluations, and enjoyment and avoidance of physical activity and sport. Undergraduate students (N = 579) completed a survey assessing demographics, and the variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 52 publications
3
43
0
Order By: Relevance
“…Consistent with prior literature findings ( 10 13 ), weight stigma in the present study was found to be negatively associated with PA. Previous research suggests that weight stigma is a variable that lowers individuals' motivations to exercise and subsequently results in low levels of PA among individuals ( 10 13 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Consistent with prior literature findings ( 10 13 ), weight stigma in the present study was found to be negatively associated with PA. Previous research suggests that weight stigma is a variable that lowers individuals' motivations to exercise and subsequently results in low levels of PA among individuals ( 10 13 ).…”
Section: Discussionsupporting
confidence: 93%
“…Previous research suggests that weight stigma is a variable that lowers individuals' motivations to exercise and subsequently results in low levels of PA among individuals ( 10 13 ). Indeed, Cheng et al ( 14 ) and Fung et al ( 15 ) found that Hong Kong university students were likely to have weight stigma effects in relation to their intention to engage in PA. Because individuals having weight stigma (either weight-related self-stigma or perceived weight stigma) may want to escape from other individuals' judgements, one coping strategy that is employed is not to exercise in front of them ( 10 15 ). More specifically, those who have weight stigma issues may feel like they are being laughed at and/or derided by others when they exercise.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research with low SES groups has indicated that lack of time plays a role [19][20][21][22] together with a lack of enjoyment of physical activity [20], poor health [15], and being overweight or obese [23]. People who are inactive report that negative emotions driven by poor past experiences or fear, worry, and anxiety about their physical competency are barriers to physical activity [24], and people who are overweight or obese experience stigma trying to exercise leading to exercise avoidance [19,[25][26][27][28]. Thus, emotions play an important part and may influence whether inactive or overweight individuals undertake and maintain physical activity.…”
Section: Introductionmentioning
confidence: 99%